THE BASIC PRINCIPLES OF BUILDING TRADING STRATEGIES - Aleksandr Kalashnikov; Sophia Golub; Victoria Ivashina (Вестник Северо-Кавказского федерального университета, 2022)
The article presents a complex author's study of the creation, launch and use of automated trading systems in stock, futures, FOREX, index and other markets. Methods of constructing a trading strategy are described, options for entering the market at a moment profitable for the participant are analyzed. The types of the most used strategies in the markets are given.